œBerbaur Tapi Tidak Lebur: Membentuk dan Mempertahankan Identitas Religius pada Mahasiswa Aktivis Dakwah Kampus (œMixing but not melting: Forming and Maintaining Religious Identity among Islamic Activists on Campus) - Muhammad Syafiq (Universitas Negeri Surabaya, 2012)
This study aimed at revealing how religious identity is formed and maintained among Islamic student activists in higher education. The implications of the religious identity on their social relations to other students and larger society were also discussed. A qualitative approach with a phenomenological method was employed. Four participants were recruited based on their long engagements in Da'wa movements in campus and significant roles they played in the movement. Data were collected through semi-structured interviews. The results show three dominant themes, namely motivation to join the Da'wa movement, the process of religious identity formation, and strategies to maintain the identity. In general, this study concluded that the initial factors that encourage the participants' involvements in Da'wa movement in higher education is the desire to feel an emotional bond of kinship based on religious values. After joining the movement, most participants developed their self-perception as a 'minority' with all its consequences. Furthermore, the need to recruit as many common Muslim students as possible for joining in their 'minority community' raise the tension between maintaining their 'exclusive' identity or answering the requirement of making relations inclusively in order their religious messages to be received by wider students.Abstrak: Penelitian ini bertujuan untuk mengungkap bagaimana identitas religius aktivis dakwah kampus terbentuk, strategi untuk mempertahankan identitas tersebut, dan apa implikasinya dalam interaksi sosial aktivis dakwah. Penelitian ini menggunakan pendekatan kualitatif dengan metode fenomenologi. Subjek penelitian ditentukan secara purposif dengan mempertimbangkan lama keterlibatan dan peran yang dimainkan dalam gerakan dakwah kampus. Data dikumpulkan melalui wawancara semi-terstruktur. Hasil penelitian ini menunjukkan tiga tema dominan, yaitu motivasi bergabung dalam gerakan dakwah, pembentukan identitas aktivis dakwah, dan strategi mempertahankan identitas. Secara umum penelitian ini menyimpulkan bahwa faktor awal yang mendorong keterlibatan partisipan dalam gerakan dakwah adalah keinginan untuk merasakan ikatan emosional kekeluargaan yang dipersepsi sebagai 'tanpa pamrih' karena berlandaskan nilai religius. Stelah menjadi anggota komunitas dakwah, para partisipan mengembangkan persepsi diri mereka sebagai 'minoritas' dengan segala konsekuensinya. Selanjutnya, motivasi untuk mengajak sebanyak mungkin mahasiswa lain untuk bergabung dalam komunitas minoritas tersebut membuat para aktivis dakwah berada dalam ketegangan antara tetap menjaga identitas 'eksklusif' dengan tuntunan untuk bergaul luas secara inklusif agar pesan dakwah bisa diterima.